Basic Life Support and automated external defibrillator:: effectiveness of laypeople training executed by a university extension project - de Souza Ramos Filho, Angelo; de Siqueira Silveira , Fernanda; Martins de Andrade, Gustavo; Che Barbosa Paiva, Daniel (LAJEC - Latin American Journal of Emergency Care, 2024)
Objective: To analyze the effectiveness of Basic Life Support training and automated external defibrillator management by laypeople through an university extension project. Methods: Questionnaires were applied to two groups of people who were analyzed, by statistical tests, according to the number of correct answers before and after the training carried out by the project, with the Basic Life Support in the Hands Only model and automated external defibrillator handling. In addition, a questionnaire was applied to analyze the sociodemographic impact on the sample. Results: According to the analytical test carried out, only the trained group, in relation to the control group, showed a significant difference in the average, minimum of 1.53 and maximum of 2.49 points, considering the paired data. The sociodemographic values analyzed were not significant in this test. The sociodemographic values analyzed were not significant in this test. Conclusion: The project proved to be effective in training laypeople, obtaining a significant gain in grades compared to untrained laypeople. It is noteworthy that the use of learning measures in laypeople should be expanded in order to disseminate knowledge on the subject and increase the chance of survival of a cardiopulmonary arrest victim.